HUBUNGAN ANTARA EFIKASI DIRI DENGAN PROKRASTINASI AKADEMIK MAHASISWA PENDIDIKAN IPS DI UNIVERSITAS TANJUNGPURA PONTIANAK - Maulidyanti Anisya Putri; Aminuyati Aminuyati; Venny Karolina (Universitas Tanjungpura, 2022)
This study aims to determine the level of student self-efficacy, the level of student academic procrastination, differences in self-efficacy in male and female students, differences in academic procrastination in male and female students, and to determine the relationship between self-efficacy and academic procrastination for students of Social Studies Education. FKIP Untan. The approach used is quantitative with survey research methods. The data collection tool used is a questionnaire or questionnaire. The number of participants in this study were 100 students from the Social Studies Education study program. The data analysis technique used is descriptive statistics, independent sample t-test, and product moment correlation test. The results showed that the average level of self-efficacy of Social Studies Education students was in the high category (76.58%), the level of academic procrastination was in the medium category (63.62%), there was no significant difference in the self-efficacy of male and female students, there is no difference in procrastination in male and female students, and there is a significant negative relationship between self-efficacy and academic procrastination (p= 0.00 and r = -0.41) in students of the Social Sciences Education study program, Tanjungpura University, Pontianak.